The Efficacy of Role-Playing Techniques in Fostering Arabic Speaking Proficiency Among Female Learners - Nurul Fauzah (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
This study examines the effectiveness of role-playing techniques in enhancing Arabic speaking proficiency among female learners in an Islamic boarding school context. The study aims to (1) determine the extent to which role-playing improves learners’ oral performance and (2) identify the speaking components most affected by this pedagogical intervention. Adopting a mixed-methods approach, the research combines quantitative pre- and post-test measures with qualitative classroom observations and semi-structured interviews. The quantitative findings demonstrate a statistically significant improvement in overall speaking proficiency (p < .001), with the greatest gains observed in learners’ self-reported communicative confidence, followed by fluency and vocabulary use. Qualitative evidence further reveals reduced speaking anxiety, heightened motivation, and increased classroom engagement, indicating that role-playing creates a supportive affective and communicative learning environment. Grounded in Communicative Language Teaching (CLT) and Vygotsky’s Sociocultural Theory, the findings suggest that gender-sensitive, interactive pedagogy facilitates meaningful participation and expressive language use among female learners. The study concludes that role-playing is not merely an instructional activity but a pedagogical strategy that effectively bridges linguistic competence and communicative confidence. These findings offer practical implications for Arabic language educators seeking to implement experiential and culturally responsive speaking instruction in female Islamic educational settings.